VD_FINDINFO Jug / 2016 / 99 vom 20. Januar 2016 - VD Tribunal cantonal (2016)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, CONTRAVENTION, AMENDE | 26 al. 1 LCR, 26 LCR, 90 al. 1 LCR, 90 al. 2 LCR, 90 LCR